Thermodynamic Properties of the Isomers of [HNOS], [HNO2S], and [HNOS2] and the Role of the Central Sulfur. Issue 33 (14th July 2014) - Méndez, Mariano; Francisco, Joseph S.; Dixon, David A.
Abstract Simple hydrides of compounds containing N, S, and O are of significant interest due to the role that they play in atmospheric chemistry and in biological pathways. There is a lack of quantitative thermodynamic data on these compounds. We have used a reliable computational chemistry approach based on valence CCSD(T) calculations extrapolated to the complete basis set limit with additional corrections to predict the heats of formation and bond dissociation energies of such compounds. The results show that compounds with the ability of the central S atom to effectively expand its valency leads to more stable isomers and, as a consequence, that those with the NSO structural motif are thermochemically more stable than those with the SNO motif. In addition, SO bonds are preferred over NO bonds.